Association Study and Expression Analysis of Stearoyl Co-A Desaturase as a Candidate Gene for Fatty Acid Composition in Indonesian Crossbred Chickens - Gunawan, Asep; Nurajizah, Eva Siti; Listyarini, Kasita; Furqon, Ahmad; Bilyaro, Woki; Sumantri, Cece; Jakaria,; Akter, Syeda Hasina; Uddin , Muhammad Jasim (International Journal of Poultry Science, 2018)
Background and Objective: The stearoyl-CoA desaturase (SCD) gene encodes an enzyme involved in fatty acid (FA) biosynthesis. The aim of the present study was to investigate the association and expression of SCD as a candidate gene for FA composition in Indonesian crossbred chickens. Materials and Methods: Sixty-two Indonesian crossbred, unsexed chickens (F2 Kampung×broilers) were used. FA composition was measured at 12 weeks of age from thigh meat of crossbred chicken. Results: A single nucleotide polymorphism in coding region c.17492542 C>G of SCD was associated with FA composition, including both unsaturated [linoleic (C18:2n6c) and eicosadienoic (C20:2) acids] and saturated [lauric acid (C12:0)] forms. SCD mRNA expression analysis in liver revealed 6 chickens with extremely high and low FA compositions, of them, high FA birds (n = 3) had higher unsaturated and lower saturated FAs, while the low FA group (n = 3) had lower unsaturated and higher saturated FA levels. SCD expression was higher (p